Estudo do comportamento do titânio recoberto com apatita e dopado com nanopartícula de prata e óleo essencial - Prado, Deborah Gouvêa (2019)
Titanium is an example of biomaterial used in orthopedic and orthodontic implants, because it has good corrosion resistance and excellent biocompatibility. Thus, studies seek to obtain a titanium coating to improve the adhesion between the bone and the implant, by modifying the metal surface. The objective of this work was to study the corrosive effect using as means the synthetic saliva and the 1.5 SBF (Simulated Body Fuid), in addition to studying the bactericidal effect of the apatite layer on the silver nanoparticle and the essential oil formed on the surface of the titanium. The coating with hydroxyapatite was performed by the biomimetic method. After the immersion, some samples were submitted to the solution of silver nanoparticle and other/s in essential oil of lemongrass. By the scanning electron microscopy of the Ti c.p. With addition of silver, it is possible to observe the formation of homogeneous layers of small compacted globules. From the corrosion test it was possible to observe that in that in the medium of 1.5 FBS, as well as in synthetic saliva, coating with hydroxyapatite and silver nanoparticle bactericides and lemongrass oil improved the corrosive properties of the sample.